Assessment of Engineering Properties of Artificial Aggregate Prepared From Canal Silt - Safdar Iqbal; Beenish Jehan; Fasih Ahmed Khan; Hassan Nasir (Sir Syed University Research Journal of Engineering and Technology)
In this research the canal silt from the Kabul River Canal was recycled to manufacture artificial aggregate. For making artificial aggregates three batches were prepared each of dry weight of 100kg. The composition of artificial aggregate is Polyvinyl Alcohol (PVA), Ordinary Portland Cement (OPC) and Silt was mixed in different proportions (by weight). Three batches were made having values of PVA varying from 0, 1 and 2 percent, cement content was 20, 19 and 18 percent respectively, and the quantity of silt used was kept constant (80%) in each batch. Samples were prepared from these three different batches and were cured for 28 days. After completion of the curing time, they were crushed to get the desired course aggregate. A number of tests were performed to check the viability of artificial aggregates for being used as a lightweight aggregate. Shape and particles size distribution properties of artificial aggregates were as that of the natural aggregate but not satisfactory at high silt content. The reductions in the specific gravity of the artificial aggregate were also observed compared to natural aggregates.